2013
DOI: 10.1007/s00425-013-1854-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal progress of programmed cell death in the developing starchy endosperm of rice

Abstract: Programmed cell death (PCD) is the genetically regulated disassembly of cells, and occurs in the endosperm of cereals during seed maturation. Since PCD determines the lifetime of cells, it can affect endosperm growth and, therefore, cereal yield. However, the features and mechanisms of PCD in the developing starchy endosperm in the Poaceae remain unclear. In the present study, we investigated the characteristics of PCD in developing starchy endosperm of rice (Oryza sativa L.) by fluorescence microscopy, focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 26 publications
3
31
0
Order By: Relevance
“…The deltaVPE with caspase-1-like activity is required for seed coat formation (Nakaune et al, 2005). In rice, PCD mediating development of starchy endosperm is associated with the caspase-like protease (Kobayashi et al, 2013). Recently, several caspase-like-related genes encoding metacaspases (OsMC1-8) and VPEs (OsVPE1-4) (Deng et al, 2011) have been reported in rice.…”
Section: Researchmentioning
confidence: 99%
“…The deltaVPE with caspase-1-like activity is required for seed coat formation (Nakaune et al, 2005). In rice, PCD mediating development of starchy endosperm is associated with the caspase-like protease (Kobayashi et al, 2013). Recently, several caspase-like-related genes encoding metacaspases (OsMC1-8) and VPEs (OsVPE1-4) (Deng et al, 2011) have been reported in rice.…”
Section: Researchmentioning
confidence: 99%
“…It should be noted that, in contrast to what occurs during perisperm PCD where DNA fragmentation is coupled to VEIDase activity, in barley endosperm, DNA fragmentation and VEIDase activity are uncoupled. VEIDase activity has also been detected in rice by Kobayashi et al () together with other PCD hallmarks such as mitochondrial membrane permeabilization. According to Lan et al () the earliest sign of PCD in rice starchy endosperm is the nuclear fragmentation, which starts as soon as cellularization is completed.…”
Section: Pcd and Endosperm Developmentmentioning
confidence: 75%
“…To date, PCD during seed development has been well‐studied in the nucellus of ricinus (Greenwood et al ), Sechium edule Sw (Lombardi et al ), wheat (Domínguez et al ) and barley (Radchuk et al ) and also in the endosperm of quinoa (López‐Fernández and Maldonado ), rice (Lan et al ; Kobayashi et al ), wheat (Young and Gallie ), maize (Young and Gallie ) and barley (Borén et al ). Figure summarizes the main events studied in the seeds of such species, most of which are involved in the activation of proteases and the induction of specific nucleases.…”
Section: Introductionmentioning
confidence: 99%
“…PCD is the genetically regulated disassembly of cells, and commonly occurs in the endosperm of cereals during grain filling. In developing starchy endosperm of rice, PCD is characterized by the involvement of mitochondrial signaling, probably by releasing signal molecules such as cytochrome c and ROS from mitochondria (Kobayashi et al 2013). (2) ABA plays a key role in initiating a network of signaling cascades concerning multiple protein kinases, such as ATH1 (a transmembrane histidine kinase receptor), mitogen-activated protein kinases (MAPKs), calcium-dependent protein kinases (CDPKs) and sucrose non-fermenting-1-related protein kinases (SnRKs) (Semenov and Halford 2009 and references cited herein).…”
Section: Abamentioning
confidence: 99%